arcsinx=-arccosx+C吗?因为(arcsinx)'=(-arccosx)'=1/[(1-x²)^(1/2)],所以arcsinx=-arccosx+C?请问这样对吗?

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 16:23:33
arcsinx=-arccosx+C吗?因为(arcsinx)''=(-arccosx)''=1/[(1-x²)^(1/2)],所以arcsinx=-arccosx+C?请问这样对吗?arcsi

arcsinx=-arccosx+C吗?因为(arcsinx)'=(-arccosx)'=1/[(1-x²)^(1/2)],所以arcsinx=-arccosx+C?请问这样对吗?
arcsinx=-arccosx+C吗?
因为(arcsinx)'=(-arccosx)'=1/[(1-x²)^(1/2)],所以arcsinx=-arccosx+C?
请问这样对吗?

arcsinx=-arccosx+C吗?因为(arcsinx)'=(-arccosx)'=1/[(1-x²)^(1/2)],所以arcsinx=-arccosx+C?请问这样对吗?
对的,而且C=pi/2